EXPLORATION OF POSTMODERNISM IN JEMBER FASHION CARNIVAL IN THE ERA OF TECHNOLOGICAL DISRUPTIONS - Bunga Surawijaya Ningsih; Kartika Bina Kasih; Nurul Hasan; Nova Saha Fasadena (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The ideas that replace the concepts of the contemporary era are known as postmodernism. This research provides a theoretical analysis of postmodern ideas, which are the basis for the emergence of contemporary artistic ideas and are reinforced by the increasing tendency of young Indonesian artists to combine contemporary aesthetic styles with the visual power of traditional culture. As a result, the works created are global in nature but retain their traditional values. The